The Change of the Vilnius City Police in the Late 18th–Early 19th Centuries: Officers, Structure, Functions - Pugačiauskas, Virgilijus (History / Istorija, 2022)
Abstract. The article analyses the main problematic aspects of the development of the Vilnius City Police as a significant factor influencing the perspective of self-government functioning. It is explained how the organizational principles of the city police of the Russian Empire were started to be applied in the city of Vilnius. It is claimed that the police, having broad and clearly undefined competencies, limited the self-government’s opportunities for independent activity and created favorable conditions for the management institutions of the Vilnius Governorate to ensure comprehensive control of the activities of the city’s self-government institution, the magistrate, in a short period of time.